An approach to giant cell arteritis (GCA) - Clifford, Alison (Henry Stewart Talks, 2018)
Pathogenesis of GCA, Common presenting features, Role of biopsy and diagnostic imaging studies, Review of available therapies, including steroid-sparing options, Survival and risk of end-organ damage
Reviewed at 2024/10/22